2016
DOI: 10.1016/j.medici.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

sFlt-1, PlGF, sFlt-1/PlGF ratio and uterine artery Doppler for preeclampsia diagnostics

Abstract: The sFlt-1/PlGF ratio and PlGF are superior to sFlt-1, UAPI and UARI for preeclampsia diagnosis. For early-onset preeclampsia diagnostics either sFlt-1 or PlGF is sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…31 In addition, unlike the present study, other reports have shown that circulating sFlt-1 levels were significantly higher in early-onset preeclampsia than in late-onset preeclampsia. 3234 In the present study, serum sFlt-1 levels in patients with severe preeclampsia were significantly higher than those in the mild preeclampsia group, which was comparable to a previous report. 35 Finally, to the best of the authors’ knowledge, the present study demonstrated for the first time that serum 25(OH)D was inversely correlated with sFlt-1 levels in female patients with preeclampsia.…”
Section: Discussionsupporting
confidence: 90%
“…31 In addition, unlike the present study, other reports have shown that circulating sFlt-1 levels were significantly higher in early-onset preeclampsia than in late-onset preeclampsia. 3234 In the present study, serum sFlt-1 levels in patients with severe preeclampsia were significantly higher than those in the mild preeclampsia group, which was comparable to a previous report. 35 Finally, to the best of the authors’ knowledge, the present study demonstrated for the first time that serum 25(OH)D was inversely correlated with sFlt-1 levels in female patients with preeclampsia.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, the highest sensitivity and specificity for preeclampsia had SFlt-1/PlGF and PlGF with the cut-off values of ≥35 (sensitivity of 95.8% and specificity of 96.2%, respectively) and ≤138.6 pg/mL (sensitivity of 95.8% and specificity of 93.7%, respectively). 12 Thus sFlt-1/PIGF has a high negative predictive value for ruling out preeclampsia in the patients who are at risk for the disease. This test is simple and easily reproducible.…”
Section: Discussionmentioning
confidence: 98%
“…[15] In another study, sensitivity/specificity rates of sFlt-1 and PGF to predict preeclampsia were 85/66% and 96/94%, but these rates increased up to 96/97% when sFlt-1 and PGF were proportioned (sFlt-1/PGF). [18] However, these biomarkers are very expensive and they still need confirmation. Simple, widespread and inexpensive laboratory findings are needed to establish the diagnosis of preeclampsia and to determine its severity.…”
Section: Discussionmentioning
confidence: 99%